Pelatihan Manajemen Keuangan Sederhana bagi Pelaku UMKM di Dusun Karang Lamper - Ni Kadek Kristiani Wahyuning; Habibi Habibi; Dewi Kusumasanthi; I Komang Widya Purnamayasa (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Simple financial management training is an effort to improve the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) in Karang Lamper Hamlet, Jagaraga Indah Village, Kediri District, West Lombok Regency. This program is motivated by the poor practice of financial recording, where most entrepreneurs still rely on memory and mix personal and business finances. This activity aims to improve the ability of MSMEs to record income, expenses, and calculate business profits independently. The implementation method includes initial observation, socialization, simple cash book training through personal visits, and evaluation by distributing questionnaires and directly checking the results of the recording. A total of 10 MSMEs participated in this program. The evaluation results showed that 70% of participants began recording finances regularly, 100% felt helped in managing business finances, and 90% considered the cash book easy to use. This program has proven effective in building awareness and skills in financial recording, although further assistance is still needed to maintain consistent recording. The personal approach-based training has proven relevant to local needs and can have a positive impact on the sustainability of micro-enterprises in rural areas.